A relação entre Estado e a organizações não governamentais no contexto alagoano (1990-2018) : percepções dos profissionais da sociedade civil organizada - Cardeal, Janine Oliveira (2019)
The object of study of this research was to think about the problematic: What are the implications of the relationship with the State for Non-Governmental Organizations in the context of Alagoas according to the perceptions of professionals of organized civil society? In this sense, the central objective is to investigate from the meanings constructed by the subjects of the research the weakening of the role of the mentioned institutions with respect to the partnerships established with the public power. The research is concerned with Non-Governmental Organizations (NGOs) - inserted in the Third Sector - whose focus is related to the field of education, therefore in spaces that offer non-school educational processes. With special care, the relationship between the State and NGOs in the Alagoan social fabric was analyzed, identifying the implications of this approach for the weakening process of nongovernmental institutions. In order to carry out the research, the following methodological procedures were taken: a) a cadastral survey was carried out of the institutions operating in the state of Alagoas; b) the mapping was delineated according to the mesoregions of the Alagoas territorial base; c) selected three organizations located in three municipalities according to the mesoregions of Alagoas and that develop or developed educational processes in partnership with the State in order to analyze the terms of these relations; d) the production of scientists who dealt with the themes: State, Third Sector and NGOs were discussed, namely: Bava (2003); Cardoso (1999); Carvalho (1998), Coutinho (2006), Fernandes (1994), Gramsci (2000), Gohn (2010), Landim (2002), Montaño (2002), Nogueira (2009), Petras (2001); Rodrigues (1998), Souza and Rodrigues (1993) and Vieira (1998), among others. In view of the possibilities of the qualitative methodological approach, the multisite study (YIN, 2015) provided an in-depth knowledge of the realities (DIEHL, TATIM, 2004). In this sense, we interviewed the professionals who carry out educational activities in the NGOs observed, which were constituted subjects of the research. Thus, in detail: three managers were interviewed, as well as questionnaires were applied with sixteen subjects involved in the work development in the investigated institutions. The results indicate that organizations as service providers are co-opted to develop actions from public resources, and they play the role of executing actions. From this perspective, they behave as a complement to the arm of the State to meet urgent social issues. This conception, in which NGOs behave as responsible for fulfilling a complementary role, corroborates the process of weakening the social role played by such entities. With regard to Education, it was observed that the expansion of the actions of these institutions in the social field through educational actions is correlated to the process of reform of the Brazilian State in the provision of public services and in the consequent insertion of Alagoas in this process in a subalternized way. It is argued that NGOs need to reflect on the social role they play in dealing with demands, in particular by assessing the risks of approaching the state sphere, considering that they can not behave in a subordinate and dependent manner. In this way, they can act in the sense of potentializing and distributing better roles and attributions, since it is not constitutional that such organizations occupy the secular role of the republican State in guaranteeing and effecting the right of the citizen.